Estimation of foliage moisture content using near infrared reflectance spectroscopy (Agricultural and Forest Meteorology, 2004)
This study explored the relationships between the initial moisture content of leaves and their spectral properties when dry. Foliage moisture content (FMC in % dry-weight (DW)) was measured in 864 samples of eight common Mediterranean tree and shrub species from two sites during the summers of 2001 and 2002. All samples were dried, ground and scanned using a near infrared reﬂectance spectrophotometer. There were close relationships between FMC and foliage absorbance in the 400–2500 nm spectral range. Calibrations involving search for predictive relationships between spectral data and FMC were performed using partial least squares (PLS) regression that took into account all the spectral information. Calibration on FMC in each species from each year was predictive when a sufﬁciently large range of FMC values were available (R 2 = 0.93–0.99, standard error of cross-validation (SECV) = 2–7%). Moreover, calibration on FMC in all species combined, for each year or for both years together, was also predictive (R 2 = 0.92–0.95, SECV = 7%). It was thus possible to estimate the initial moisture content of a fresh foliage sample from its spectral characteristics when dried, whatever the species. However, mean foliage spectral absorbance changed from 1 year to the other. Consequently, FMC in leaf samples from each year was not estimated with accuracy when using the calibration established on samples from the other year but was accurately estimated when using the calibration established on samples from both years together. These close relations between dried foliage spectral data and FMC meant that some biochemical properties of the leaves associated with the changes in leaf water status caused changes in spectral reﬂectance which was preserved in the dried samples.

The use of near infrared reflectance spectroscopy to study chemical changes in the leaf litter consumed by saprophagous invertebrates (SOIL BIOLOGY & BIOCHEMISTRY, 2001)
Chemical changes in holm oak leaf litter that was consumed by the millipede Glomeris marginata were studied using near infrared reflectance spectroscopy. Compared to leaf litter, faecal pellets were significantly richer in lignin and poorer in nitrogen and readily assimilable constituents. The C:N ratio was significantly higher in the faeces. A NIRS-predicted index of litter decomposability was found to be lower in the faeces than in uneaten litter. (C) 2001 Elsevier Science Ltd. All rights reserved.